Electrochemical Oxidation of Syngas on Nickel and Ceria Anodes. (20th February 2017) - Tabish, A.N.; Patel, H.C.; Aravind, P.V.
Abstract: Fuel flexibility of solid oxide fuel cells enables the use of low cost and practical fuels like syngas. Understanding of the oxidation kinetics with syngas is essential for proper selection of anode material and its design optimization. Using nickel and ceria pattern anodes, we study the electrochemical oxidation of syngas in both dry and wet environments. In dry environment, the polarization resistance of CO oxidation drops drastically with the addition of small amounts of hydrogen to CO gas stream. In wet environment (4 % moisture), the polarization resistance of CO is only slightly higher than syngas and hydrogen. Observation in the first case is related to the hydrogen preferential oxidation whereas latter is a combined effect of water gas shift reaction and preferential oxidation of hydrogen. Kinetic modeling is also carried out to understand hydrogen and CO co-oxidation. Simulation suggests that CO, besides hydrogen, may also electrochemically oxidize depending upon its concentration in the syngas. At higher concentration, CO electrochemical oxidation may be non-negligible especially in case of ceria anodes.